Improved Modified Class of Estimators in Estimating the Population Mean - Dansawad, Napattchan (วารสารวิทยาศาสตร์และเทคโนโลยี หัวเฉียวเฉลิมพระเกียรติ, 2022)
In this present paper, following the work of Yadav et al. [1], the author creates alternative class of estimators for estimating the population mean in situation of positive and negative correlations between supplementary and interested variables under simple random sampling without replacement (SRSWOR) scheme. Furthermore, this paper also introduces a modified class of estimators based on combination of alternative class of estimators and unbiased estimator. The expressions for the bias, Mean square error (MSE), and Minimum mean square error (MMSE) of all introduced estimators were considered. Both theoretical and numerical analysis were encouraging and supporting the performance of all introduced estimators for the mean estimation. The MSE and Percent relative efficiencies (PREs) were used as criteria for efficiency comparison between the new estimators and other existing estimators.